Identification and imaging of miR-155 in the early screening of lung cancer by targeted delivery of octreotide-conjugated chitosan-molecular beacon nanoparticles - Hai-Zhen Zhu; Jing Hou; Yi Guo; Xin Liu; Fei-Long Jiang; Guang-Peng Chen; Xiu-Feng Pang; Jian-Guo Sun; Zheng-Tang Chen (Taylor & Francis Group, 2018)
Lung cancer is still the most common cancer globally. Early screening remains the key to improve the prognosis of patients. There is currently a lack of specific and sensitive methods for early screening of lung cancer. In recent years, studies have found that microRNA plays an important role in the occurrence and development of lung cancer and become a biological target in the early diagnosis of lung cancer. In this study, lung cancer cells, subcutaneous xenografts of lung cancer in nude mice, and Lox-Stop-lox K-ras G12D transgenic mice were used as models. The transgenic mice displayed the dynamic processes from normal lung tissue to atypical hyperplasia, adenomas, carcinoma in situ and lung adenocarcinoma. It was found that miR-155 and somatostatin receptor 2 (SSTR2) were expressed in all the disease stages of transgenic mice. Through molecular beacon (MB) technology and nanotechnology, chitosan-molecular beacon (CS-MB) nanoparticles and targeted octreotide (OCT) were conjugated and synthesized. The octreotide-conjugated chitosan-molecular beacon nanoparticles (CS-MB-OCT) can specifically bind to SSTR2 expressed by the lung cancer cells to achieve the goal of identification of lung cancer cells and imaging miR-155 in vivo and in vitro. Fluorescence imaging at different disease stages of lung cancer in Lox-Stop-lox K-ras G12D transgenic mice was performed, and could dynamically monitor the occurrence and development of lung cancer by different fluorescence intensity ranges. The current research, in turn, provides new idea, new method, and new technology for the early screening of lung cancer.